Monitoring the sensing response towards CO detection of ferroelectric La doped BiFeO3-based semiconductors - Pinto, O.M. [UNESP]; Acero, G. [UNESP]; Aguiar, E.C.; Berengue, O.M. [UNESP]; Simões, A.Z. [UNESP] (Elsevier, 2025)
Over the past decade, bismuth-based materials have been extensively investigated for diverse applications, including gas sensing. To advance this field, a comprehensive understanding of the electrical properties of La-doped BiFeO3 synthesized via the microwave-assisted method in a CO-rich atmosphere is essential. In this study, phase-pure La-doped BiFeO3 thin films were characterized under CO exposure, emphasizing the impact of rare-earth substitution on their electrical behavior. The samples were designated as BFO (undoped) and BFO08, BFO015, and BFO030 for La doping concentrations of 8 %, 15 %, and 30 %, respectively. La incorporation into the BiFeO3 matrix enhances the nucleation rate, leading to reduced crystallite sizes. In contrast, the undoped BiFeO3 exhibits fewer nucleation events, resulting in larger particles with slower growth rates but reduced agglomeration. The La doping improves the ferroelectric properties, reduces leakage currents, and increases polarization. The presence of charged oxygen vacancies, compensatory electronic charge carriers, and mixed-valence iron states (Fe2+/Fe3+) is associated with the higher leakage current observed in undoped BFO. Regarding CO gas sensing performance, the La-doped BiFeO3 films exhibit significantly faster response times (0.17 s and 0.40 s for BFO08 and BFO015, respectively) compared to the undoped sample (0.91 s), highlighting their high sensitivity. Our results show that, beyond lanthanum content, microstrain and particle size significantly affect the sensing behavior and polar properties of BiFeO3, highlighting the promise of rare-earth-doped BiFeO3 for advanced gas sensors and multiferroic devices.